Synthesis and Characterization of Ternary Hetero Chelates of La(III), Pr(III), Nd(III) and Sm(III) - K. Agarwal, Suresh; Chand, Subhash (Asian Journal of Chemistry, 2010)
Ternary hetero chelates of La(III), Pr(III), Nd(III) and Sm(III) with 7-hydroxy-4-phenyl-6-(α-naphthyl)-aminomethyl coumarin (HPAC) as primary and 2-thiopyrogallol as co-ligand have been synthesised and characterised on the basis of analytical, magnetic, spectral and thermal studies. The chelates have the general formula [Ln(HPAC)(TG)X2], where Ln = La(III), Pr(III), Nd(III), and Sm(III), HPAC = 7-hydroxy-4-phenyl-6- (α-naphthyl)-aminomethyl coumarin, TG = 2-thiopyrogallol (mono deprotonated), X = Cl, NO3. The lower Λm values (4.0-4.8 moles) in DMSO indicate their non-electrolytic nature. The compounds are nonhygroscopic and air stable. They are insoluble in common organic solvents but dissolve in DMSO and DMF considerably. The magnetic moment and reflectance spectral data of the complexes suggested octahedral configuration. IR spectra of the ternary chelates showed bidentate behaviour of both the ligands. In HPAC, nitrogen atom of —NH group and oxygen of —OH group form bond with the metal ion while TG participates through the oxygen atom of —OH group and sulphur of deprotonated —SH group. All the complexes decompose endothermally at ∼430ºC with the elimination of HPAC. In the temperature range 670-730ºC, thiopyrogallol molecule is also lost and finally, a metallic oxide residue is obtained.